Motivational interventions - Karabenick, Stuart A.; Urdan, Timothy C. (Advances in motivation and achievement ;, 2014)
Researchers from a variety of disciplines are designing creative ways to apply basic research principles to solve persistent motivational problems in education. From brief interventions based on social psychological principles to multi-year collaborative projects with teachers, each of the chapters in this volume describes theory-driven projects that produce genuine benefits for students and teachers. As these and other intervention efforts gain attention, replication, and variation, new questions have begun to emerge. Can these interventions be 'scaled up" to benefit a larger number of students? Will some lose power as they lose novelty? How will these interventions work with other innovations and changes in education? How well will interventions that have been found effective with some populations generalize to other students? These interventions work best when they are targeted to a specific group at a specific point in their educational careers. So questions about scalability and generalizability are empirical questions that will certainly be examined in years to come. By compiling research on motivational interventions we hope that this volume will move this process forward.